Indoor-related microbe damage induces complement system activation in building users - Janne Atosuo; Outi Karhuvaara; Eetu Suominen; Liisa Vilén; Jari Nuutila; Tuula Putus (Innate Immunity, 2021)
In this comparative study, serum complement system antimicrobial activity was measured from 159 serum samples, taken from individuals from microbe-damaged (70 samples) and from reference buildings (89 samples). Antimicrobial activity was assessed using a probe-based bacterial Escherichia coli -lux bioluminescence system and comparison was made at a group level between the experimental and reference group. The complement activity was higher in users of microbe-damaged buildings compared with the reference group and the significant ( P  < 0.001) increase in activity was found in the classical reaction pathway. This study strengthens our notion that exposure to indoor-related microbe damage increases the risk for systemic subclinical inflammation and creates a health risk for building users.